Pembentukan Identitas Sosial Penutur Bahasa Jawa Ngapak pada Komunitas Daerah KMB Serulingmas: Sebuah Studi Kualitatif Dalam Perspektif Psikologi Sosial - Siti Nurazizah; Vidya Ajijiah; Asfia’ul Auliya; Ane Davina Larasati; Siti Hikmah (CV. Lentera Literasi Indonesia, 2026)
This study aims to understand the experiences of Javanese Ngapak dialect-speaking students in forming and interpreting their social identity through interactions in the KMB Serulingmas community at UIN Walisongo. The Ngapak language is seen not only as a means of communication, but also as a symbol of origin, cultural attachment, and personal characteristics inherent to its speakers. Using a qualitative phenomenological approach, this study involved students selected through purposive sampling and interviewed in depth to explore their subjective experiences. Data analysis was conducted using simple thematic analysis to identify patterns of meaning that emerged from the participants' stories. The results show that the use of Ngapak language provides a sense of comfort, closeness, and authenticity, especially when among fellow community members. Jokes about the Ngapak dialect often arise in social interactions, but are generally responded to with humor so that they do not interfere with self-acceptance. The Serulingmas community acts as a safe space that strengthens a sense of belonging, provides emotional support, and facilitates social adaptation in the campus environment. The novelty of this research lies in its emphasis on the psychological dimensions of Ngapak speakers in the context of regional communities, particularly in relation to emotional experiences, self-acceptance, and the process of identity negotiation. These findings contribute to the study of social psychology, especially in understanding the relationship between regional languages, group identity, and the dynamics of student social interaction.